Wildlife 2001: Populations 1992
DOI: 10.1007/978-94-011-2868-1_63
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Small Mammal Populations: A Review

Abstract: An understanding of population dynamics requires explanations for both the patterns of fluctuations and the densities at which they occur. To identify the causal mechanisms involved, we need to examine the environmental factors that impinge upon the population, the integrative responses of individuals that link changes in the environment to individual performance, and the population changes that occur as a result of shifting individual performances. A review of the literature on small mammals, mostly rodents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
1
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 73 publications
0
96
1
6
Order By: Relevance
“…Small mammalian herbivores such as the bank vole have high energy metabolism and turnover of essential nutrients. This suggests that small mammalian herbivores face a relative shortness of N and that this situation may be a potential cause for variations in population density between seasons and years (Hansson 1987, 1995, Batzli 1992, Hambäck et al 2002, Wereszczynska et al 2007. Protein requirement is a result of two components a) endogenous urinary excretion and b) fecal loss.…”
Section: Introductionmentioning
confidence: 99%
“…Small mammalian herbivores such as the bank vole have high energy metabolism and turnover of essential nutrients. This suggests that small mammalian herbivores face a relative shortness of N and that this situation may be a potential cause for variations in population density between seasons and years (Hansson 1987, 1995, Batzli 1992, Hambäck et al 2002, Wereszczynska et al 2007. Protein requirement is a result of two components a) endogenous urinary excretion and b) fecal loss.…”
Section: Introductionmentioning
confidence: 99%
“…Rodent cycles represent an enigma which has been puzzling many ecologists since Elton (1924). At least 22 hypotheses have been proposed on how the cycles are generated (Batzli 1992). Many of the hypotheses try to explain the cycle using a single factor and they have been tested by experiments in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The role of predators in controlling prey populations has been the focus of debate in the ecological literature for some time (Edminster 1939, Huffaker 1958, Errington 1963, Paine 1974, Hansson and Henttonen 1988, Hanski et al 1991, Batzli 1992, Stenseth and Ims 1993, Norrdahl 1995, Norrdahl and Korpimäki 1995, Korpimäki and Krebs 1996, Krebs 1996, Stenseth et al 1996. Other studies (Keith 1990, Krebs et al 1995, Selas et al 2002 have suggested that other factors such as food availability/ quality determine prey abundance, which may in turn drive predator numbers.…”
Section: Predationmentioning
confidence: 99%